Konsep Pasar Modal Syariah - Faozan, Akhmad (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2013)
Economic development of a country cannot be separated from the capital market. Capital market serves as a means to mobilize public funds and to search the ownership of shares of a company by selling it. Islamic capital market serves as an investment medium for Muslims in the capital market that is in line with Islamic principles. Some criteria for the establishment of the Islamic capital market are forming price fairly, the presence of perfect information, free from riba, gharar, gambling and other transactions that contradict against sharia rules. Stocks traded in the Islamic capital market should come from issuers that meet the Islamic criteria and bonds issued should use mudarabah, musharaka, ijara, istisna' and salam.